The effect of energy and protein drinks on some anthropometric and functional measures of bodybuilders (Journal of the College of Basic Education, 2022)
In this study, we try to verify and identify the characteristics of energy and protein drinks and their relationship to anthropometric and physiological measures of bodybuilding athletes, which are related to performance and achieving muscle hypertrophy, as well as their metabolic importance as a source of energy, as nutritional supplements are among the most important factors that contribute to muscle building and hypertrophy as well as the method accompanying training.